2015
DOI: 10.1007/s00436-015-4775-6
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated Tim-3/galectin-9 expressions in acute lung injury in a murine malarial model

Abstract: Malaria is the most relevant parasitic disease worldwide, and severe malaria is characterized by cerebral edema, acute lung injury (ALI), and multiple organ dysfunctions; however, the mechanisms of lung damage need to be better clarified. In this study, we used Kunming outbred mice infected with Plasmodium berghei ANKA (PbANKA) to elucidate the profiles of T cell immunoglobulin and mucin domain-3 (Tim-3) and its ligand galecin-9 (Gal-9) in the development of ALI. Mice were injected intraperitoneally with 10(6)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…However, studies in Mtb point out that the Tim-3 expression and T cell function may be pathogen-specific. Consistent with this, in murine malaria, expression of both Tim-3 and Galectin-9 were associated with liver damage and acute lung injury ( 128 , 129 ), suggesting a role in pathogenesis. It would be of interest to study if Tim-3 signaling has any role in prophylactic parasite vaccines.…”
Section: Tim-3supporting
confidence: 65%
“…However, studies in Mtb point out that the Tim-3 expression and T cell function may be pathogen-specific. Consistent with this, in murine malaria, expression of both Tim-3 and Galectin-9 were associated with liver damage and acute lung injury ( 128 , 129 ), suggesting a role in pathogenesis. It would be of interest to study if Tim-3 signaling has any role in prophylactic parasite vaccines.…”
Section: Tim-3supporting
confidence: 65%
“…Similarly, Tim-3 is expressed on a variety of immune cells, such as T cells, monocytes, macrophages, and DCs, and regulates the innate immune response39. Previous works from our laboratory have shown the upregulation of Tim-3 and Gal-9 in Pb ANKA-induced ALI in the mouse model40. In the current study, we further demonstrated that Gal-9 and Tim-3 were expressed mainly on infiltrating mononuclear cells in the lung tissues after Pb ANKA infection.…”
Section: Discussionmentioning
confidence: 98%
“…This study revealed the presence of Gal-9 in plasma in malaria patients and showed that plasma levels of Gal-9 accurately reflect the status of inflammation and recovery during malaria infection for the first time though the tissue expression of Gal-9 and Tim-3 was demonstrated in murine malaria model [ 21 , 22 ]. The elevation of Gal-9 was reported in other acute and non-acute infectious diseases such as dengue virus infection (median level was 1525 pg/mL), leptospirosis (616 pg/mL) [ 9 ], acute HIV infection (~2300 pg/mL) [ 8 ] and active tuberculosis (200 pg/mL) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Beside immune modulatory activities, Gal-9 is released from infected or damaged cells, and could act as danger signal molecules [ 9 ], by initiating inflammation as reported in murine respiratory tularaemia [ 38 ]. Moreover the Tim-3-Gal-9 expression was found to be elevated in acute lung injury in a murine malarial model [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation